TiO2 and ZnO on different supports for photodegradation of paraquat - Amin, Noraidura; Ali, Rusmidah; Wan Abu Bakar, Wan Azelee; Garif, Mohd. Nordin; Othman, Mohd. Yusuf (Penerbit UTM Press, 2007)
Paraquat dichloride has been extensively used as herbicide and the residual in the environment is known for its potential health hazard. The contaminant is non-biodegradable, toxic, stable and persistent in the environment. In this study, the photocatalytic activity of TiO2 and ZnO immobilized on different supports (cement and tile) were studied to treat this pollutant. The catalysts were prepared by two different techniques, namely, slurry method on tile and powdered scattering on cement. The degradation of paraquat was carried out in photocatalytic reactor using ultraviolet (UV) lamp at wavelength of 354 nm as a light source. The sample was illuminated for five hours. The disappearance of paraquat in the photodegradation process was monitored by UV-Vis spectrophotometer at the 400 – 200 nm region. Experiment in a dark condition and using support without catalyst was conducted as comparison control. Experimental results showed that both illumination and the catalyst were necessary for the degradation of the contaminant substrate. The data indicated that ZnO on tile is the best catalyst which 63.42% degradation was recorded compared to TiO2 on tile that was only 22.09% of degradation. Therefore, ZnO is a low cost alternative photocatalyst potential to be used for the degradation of paraquat.